A Study of cadetship training onboard Malaysian liquefied natural gas (LNG) vessel - 250102 Tan, Keat Siang (Skudai : Universiti Teknologi Malaysia, 1998)
Project Paper (Bachelor of Management Technology (Maritime Transportation)) - Universiti Teknologi Malaysia, 1998